2005
DOI: 10.1007/s10886-005-6070-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jasmonate-Induced Defenses on Root-Knot Nematode Infection of Resistant and Susceptible Tomato Cultivars

Abstract: Jasmonates, such as jasmonic acid (JA), are plant-signaling compounds that trigger induced resistance against certain pathogens and a broad range of arthropod herbivores. One goal of this study was to determine the effects of JA-dependent defenses in tomato on root-knot nematodes. Another was to determine if the artificial induction of these defenses could enhance nematode control on plants that carry Mi-1.2, a nematode resistance gene that is present in many tomato cultivars. At moderate soil temperatures, Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 52 publications
1
107
1
Order By: Relevance
“…JA enhances Mi-mediated resistance (Mi is a resistant gene in tomato) of resistant lines at high temperature (Cooper et al, 2005). However, using JA-signaling mutant jar1 (equal to coi1 of Arabidopsis) and JA biosynthesis mutant def1, it was found that endogenous JA signaling pathway is required for tomato susceptibility to RKNs (Bhattarai et al, 2008).…”
Section: The Roles Of Ja In Induced Systemic Resistance (Isr) Againstmentioning
confidence: 99%
“…JA enhances Mi-mediated resistance (Mi is a resistant gene in tomato) of resistant lines at high temperature (Cooper et al, 2005). However, using JA-signaling mutant jar1 (equal to coi1 of Arabidopsis) and JA biosynthesis mutant def1, it was found that endogenous JA signaling pathway is required for tomato susceptibility to RKNs (Bhattarai et al, 2008).…”
Section: The Roles Of Ja In Induced Systemic Resistance (Isr) Againstmentioning
confidence: 99%
“…Their study also shows a significant increase in activity of phenylalanine ammonia lyase and pathogenesisrelated protein-1 (PR-1) accumulation in roots. Cooper et al (2005), however, have indicated that application of jasmonic acid as a plant-signaling compound to tomato foliage induces systemic effects on root-knot nematode and causes significant reduction in nematode egg masses/g root tissue. They believe that the mechanism through which JA suppresses nematode infestation is ought to be transported from foliage to roots.…”
Section: Introductionmentioning
confidence: 99%
“…However, foliar pre-treatment of rice and tomato plants with salicylic acid analogs only slightly reduced susceptibility suggesting that the salicylate-mediated signaling may not have a major influence on root-knot nematode infestation of susceptible plants [25,33,34]. Conversely, foliar pre-treatments with jasmonates markedly reduced root-knot nematode infestation in both tomato and rice [25,35,36]. This negative influence of the jasmonate pathway stimulation prior to root-knot nematode infestation could potentially be consistent with a requirement for root-knot nematodes to suppress or avoid activation of the jasmonate defense signaling pathway for successful parasitism of host plants.…”
Section: Systemic Resistance and Root-knot Nematode Infestationmentioning
confidence: 98%